What do Chilean and Costa Rican psychologists believe and advise about parenting? = ¿Qué creen y aconsejan psicólogos (as) chilenos (as) y costarricenses sobre la crianza de los (as) hijos (as) ? - Castro Carrasco, Pablo Javier; Alaniz Flores, Paz Belén; Carmona Cortés, Daniela Marisol; Pizarro Rojas, Tatiana Paulina; Soto Fernández, Camila Monserrat (2017)
This research investigates the subjective theories of 12 Chilean and Costa Rican psychologists who work with children, with the purpose of describing and interpreting their explanations about child rearing. Episodic interviews wereused and analyzed using a Grounded Theory model. The interviewees point out that they use their own experience andbeliefs when advising parents. Results indicated that, according to the interviewees, the topics most frequently consulted byparents were children's high impulsivity and disciplining. The interviewees believe the most common parenting styles are theauthoritarian and the permissive ones, the latter being associated with parents' fear and anxiety.
Este estudio investigó las teorías subjetivas de 12 psicólogos(as) chilenos(as) y costarricenses que trabajan en temáticas de infancia, a objeto de poder describir e interpretar sus explicaciones sobre la crianza. Esta investigación fue de carácter cualitativo, con un diseño metodológico descriptivo-interpretativo. Se realizaron entrevistas episódicas, analizadas utilizando el modelo de la Grounded Theory (teoría fundamentada). Los participantes señalaron usar sus propiasexperiencias y creencias al aconsejar a los padres y a las madres . Según los (as) entrevistados (as) , los padres y las madres consultan principalmente sobre la impulsividad y disciplina de los (as) hijos (as) . De acuerdo a los (as) entrevistados (as), los estilos parentales más recurrentes son el autoritario y el permisivo, este último asociado con el miedo y ansiedad de lospadres y madres.
En Revista Actualidades en Psicología, Vol. 31, no. 123 (2017)
Descripción basada en el contenido visto el 19 de junio, 2023
Keywords: PSICOLOGOS -- ETICA PROFESIONAL; CRIANZA DE NIÑOS -- ASPECTOS SOCIALES -- CHILE -- ESTUDIO DE CASOS; INVESTIGACION CUALITATIVA